Promoting Long‐Term Cultivation of Motor Neurons for 3D Neuromuscular Junction Formation of 3D In Vitro Using Central‐Nervous‐Tissue‐Derived Bioink. Issue 18 (7th August 2021) - Kong, Jeong Sik; Huang, Xuan; Choi, Yeong‐Jin; Yi, Hee‐Gyeong; Kang, Junsu; Kim, Sejin; Kim, Jongmin; Lee, Hyungseok; Rim, Yeri Alice; Ju, Ji Hyeon; Chung, Wan Kyun; Woolf, Clifford J.; et al.
Abstract: 3D cell printing technology is in the spotlight for producing 3D tissue or organ constructs useful for various medical applications. In printing of neuromuscular tissue, a bioink satisfying all the requirements is a challenging issue. Gel integrity and motor neuron activity are two major characters because a harmonious combination of extracellular materials essential to motor neuron activity consists of disadvantages in mechanical properties. Here, a method for fabrication of 3D neuromuscular tissue is presented using a porcine central nervous system tissue decellularized extracellular matrix (CNSdECM) bioink. CNSdECM retains CNS tissue‐specific extracellular molecules, provides rheological properties crucial for extrusion‐based 3D cell printing, and reveals positive effects on the growth and maturity of axons of motor neurons compared with Matrigel. It also allows long‐term cultivation of human‐induced‐pluripotent‐stem‐cell‐derived lower motor neurons and sufficiently supports their cellular behavior to carry motor signals to muscle fibers. CNSdECM bioink holds great promise for producing a tissue‐engineered motor system using 3D cell printing. Abstract : Central nervous tissue decellularized extracellular matrix (CNSdECM) bioink is investigated for the 3D printing of lower motor neurons (LMNs) and fabrication of motor system. The CNSdECM bioink facilitates the growth, maturation, and axon bundle formation of LMNs. It also provides a physically stable environment, allowing long‐term cultivation of the neuromuscular tissue (NMT). The CNSdECM‐bioink‐based NMT features successful neuromuscular activity.